Lifetime progression of IgA nephropathy: a retrospective cohort study with extended long-term follow-up - Mariell Rivedal; Ole Petter Nordbø; Yngvar Lunde Haaskjold; Rune Bjørneklett; Thomas Knoop; Øystein Eikrem (BMC Nephrology)
Abstract Background IgA nephropathy (IgAN) exhibits an unpredictable trajectory, creating difficulties in prognostication, monitoring, treatment, and research planning. This study provides a comprehensive depiction of the progression of kidney function throughout the disease course, from diagnosis to a span of 36 years post-diagnosis. Methods We utilized a cohort of 400 Norwegian IgAN patients, from diagnosis to the occurrence of death, initiation of kidney replacement therapy (KRT), or the latest follow-up. Recorded proteinuria (n = 2676) and creatinine (n = 8738) measurements were retrieved. Patients were divided into subgroups based on their specific estimated glomerular filtration rate (eGFR) slopes. Results Median follow-up was 16 years. During this period, 34% of patients either died or initiated KRT. Among patients who reached endpoint, the median duration from diagnosis to the initiation of KRT or death was 8 years. Notably, 34% of the cohort exhibited a stable disease course, characterized by an eGFR decline of less than 20% between two consecutive measurements. Differences in subsequent disease trajectories among two subgroups with similar eGFR levels at diagnosis could not be accounted for by variations in treatment strategies. Among patients with proteinuria < 1 g/24 h in less than half of the measurements, KRT was five times more prevalent compared to those with more than half of the measurements recording proteinuria < 1 g/24 h (p-value = 0.001). Conclusions While a significant proportion of IgAN patients reach kidney failure within their lifetimes, outcomes vary widely. Clinical data at diagnosis offer limited insights into long-term risks. Enhanced risk stratification necessitates data collection at multiple time points.